Assessing Medication Pick-Up Rates at a Student-Run Free Health Clinic - Felix Lam; Marcus C Kaplan; Nicholas P Gazda; Megan D Shah; John A Toler; Kelly L Scolaro (Journal of Student-Run Clinics, 2017)
Background: Prescription pick up serves as the first barrier to medication adherence, in that patients must travel to a pharmacy to obtain their medications. The Student Health Action Coalition (SHAC) is a student-led, interdisciplinary, free clinic in North Carolina that serves indigent populations, who tend to have lower medication adherence. The study objectives were to compare the medication pick-up rate and time to pick up for prescriptions dispensed from SHAC Clinic with those dispensed from an external pharmacy.Methods: All â€œSHAC Paysâ€ or â€œSHAC Dispensedâ€ prescriptions written between June 17, 2014 and March 30, 2015 were included for analysis. SHAC Pays prescriptions must be picked up by the patient at an external pharmacy, while SHAC Dispensed prescriptions are dispensed directly from the clinic. Pick-up rate was measured as the percentage of written prescriptions picked up by patients and was verified using pharmacy billing records.Results: During the study period, 158 SHAC Pays prescriptions were written for 62 unique patients and 111 SHAC Dispensed prescriptions were written for 61 unique patients. The SHAC Pays pick-up rate was 58.2%, compared to 100% for SHAC Dispensed (p<0.0001). The median time to SHAC Pays and SHAC Dispensed prescription pick up was 3 days and 0 days, respectively (p < 0.0001).Conclusions: Among patients seen at a student-run free clinic, prescription pick-up rate was significantly reduced and time to pick up was delayed when medications were not dispensed to patients from clinic. On-site dispensing guarantees that patients obtain their medications and can immediately begin treatment.